Integrated mine and tailings planning: a mixed integer linear programming model. Issue 4 (3rd July 2016) - Badiozamani, M.M.; Askari-Nasab, H.
Abstract : Long-term mine planning models maximise the net present value of the extracted ore over the mine lifetime. In oil sands mining, further processing of ore material results in massive volumes of tailings slurry. Composite tailings (CT) production is one of the common technologies used for tailings dewatering. In this paper, a tailings model is developed to calculate the volume of CT. An integrated mixed integer linear programming model is developed to optimise the long-term mine planning model with respect to CT production and deposition. The model is verified by carrying out a case study on an oil sands data-set, resulting in integer solution within 1% optimality gap.